Exploring Teachers’ Pedagogical Strategies in Teaching Arabic in Multilingual Classrooms / استكشاف الاستراتيجيات التربوية للمعلمين في تعليم اللغة العربية في الفصول متعددة اللغات - Aminah Dina. F; Yuka Nakashi (IJAS: International Journal of Arabic Studies, 2025)
This study explores the pedagogical strategies employed by Arabic language teachers in multilingual classrooms, focusing on how they adapt to students’ diverse linguistic and cultural backgrounds. Using a qualitative approach, data were collected through classroom observations, interviews, and document analysis involving teachers and students from different linguistic communities. The findings reveal that teachers apply flexible, student-centered methods such as task-based learning, cooperative learning, and culturally responsive teaching. Strategies like translanguaging, differentiated instruction, and authentic assessment were identified as key tools to address varied proficiency levels and foster active language use. Despite challenges such as time constraints and resource limitations, teachers demonstrated adaptability and creativity in managing diversity and promoting inclusive learning. This study highlights the importance of pedagogical responsiveness in multilingual settings and provides insights for improving Arabic language instruction in culturally diverse environments.